Alcohol use disorders and associated chronic disease - a national retrospective cohort study from France - Michaël Schwarzinger; Sophie Pascale Thiébaut; Sylvain Baillot; Vincent Mallet; Jürgen Rehm (BMC, 2017)
Abstract Background Evidence on diseases caused by or associated with alcohol use disorders (AUDs) has been based on two meta-analyses including rather dated studies. The objective of this contribution was to estimate the risks of all-cause mortality and alcohol-attributable disease categories depending on a diagnosis of AUDs in a national sample for France. Methods In a national retrospective cohort study on all inpatient acute and rehabilitation care patients in Metropolitan France 2008-2012 (N = 26,356,361), AUDs and other disease categories were identified from all discharge diagnoses according to standard definitions, and we relied on in-hospital death for mortality (57.4% of all deaths). Results 704,803 (2.7%) patients identified with AUDs had a threefold higher risk of death (HR = 2.98; 95% CI: 2.96-3.00) and died on average 12.2 years younger (men: 10.4, 95% CI: 10.3-10.5; women: 13.7, 95% CI: 13.6-13.9). AUDs were associated with significantly higher risks of hospital admission for all alcohol-attributable disease categories: digestive diseases, cancers (exception: breast cancer), cardiovascular diseases, dementia, infectious diseases, and injuries. Elevated risks were highest for liver diseases that were associated with about two-third of deaths in patients with AUDs (men: 64.3%; women: 71.1%). Conclusions AUDs were associated with marked premature mortality and higher risks of alcohol-attributable disease categories. Our results support the urgent need of measures to reduce the burden of AUDs.